Selection of Adjusters for Temperature Adjustment in Industrial Ovens - Iskandarov Nodir Botir oʻgʻli; Gʻaybullayev Ogʻabek Shokir oʻgʻli; Ismatov Otabek Elmurod oʻgʻli; Ibragimov Islomnur; Xudoyqulov Sherobod (Scientific Trends, 2023)
This article emphasizes the significance of precise temperature control in industrial ovens for optimal product quality and process efficiency in manufacturing. It reviews key considerations for selecting temperature adjusters, covering adjustment methods like on/off, proportional, integral, derivative, and PID control. The discussion includes criteria for choosing between pneumatic, electronic, and digital adjusters, as well as insights into installation factors, tuning procedures, and common issues. The article underscores the importance of understanding oven thermal characteristics and control objectives, enabling engineers to effectively evaluate and deploy temperature adjusters for robust oven control.
Keywords: Industrial ovens, Temperature control, Manufacturing processes, Precise regulation, Heating, Drying, Curing, Baking, Temperature adjusters, On/off control, Proportional control, Integral control, Derivative control, PID control, Pneumatic adjusters, Electronic adjusters, Digital adjusters, Installation factors, Tuning procedures, Common